Heterogeneity of illegal markets: A book review essay - Hamish Richardson (Journal of Illicit Economies and Development (JIED), 2019)
Literature on the economic-sociology of illegal markets is progressing convincingly, as scholars identify the need to investigate illegality through the perspective of the market, as well as through the perspective of the actor. In this book review essay, two recent publications are reflected upon: The Architecture of Illegal Markets: Towards an Economic Sociology of Illegality in the Economy (Beckert and Dewey, 2017) and Illegal Markets, Violence, and Inequality: Evidence from a Brazilian Metropolis (Daudelin and Ratton, 2018). While the books undertake a different journey through the field of illegal markets, they reach the same theoretical destination, concluding that illegal markets are not homogenous and cannot be boxed into preconceived generalisations.
Keywords: 330; Illegal markets; drug markets; Brazil; violence; drug policy